PERANCANGAN ALAT PEMBELAJARAN KUNCI GITAR BERBASIS ARDUINO DAN ANDROID - Haris Tri Saputra; Astri Simaremare; Suwarti - (Universitas Putera Batam, 2019)
Science and technology are moving, developing in the business world and have significance to human life. This is done with the various facilities provided and provided by companies. One of the technologies used today in the music world is in musical instruments, where the author wants to use tutorial system using Chord on guitar instrument for beginner who want to learn to use guitar, so for beginners do not bother anymore to learn together and know the Chord on a guitar instrument, because the musical instruments that are already under the LED light on each fred guitar that is located under each strings of the guitar.